Analisis Pelaksanaan Asas Itikad Baik Dalam Perjanjian Kredit Secara Lisan dengan Jaminan Gadai Mobil (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
In general, when someone applies for a loan to a financial institution such as a bank or company, they will usually make an agreement that has been approved by both parties. However, it often happens that agreements are only based on verbal agreements, without being written. The aim of this research is to analyze the validity of verbal credit agreements using a car as collateral, as well as to examine whether the principle of good faith is applied in the agreement. This research is empirical legal research that uses primary and secondary data obtained from field research, literature and statutory regulations related to the issues raised. Data collection techniques are carried out through recording and documentation. This data is then analyzed and presented qualitatively. The research results show that the credit agreement made verbally between Party 1 and Party 2 meets all the requirements necessary to be considered valid in accordance with Article 1320 of the Civil Code (KUHPerdata). There was an agreement to borrow money using a Toyota car as collateral. Party 1 has also carried out its obligations in good faith in accordance with the agreement made together with Party 2, without any violations. Party 1 repaid 30% of the total loan to Ketut within 5 months, with loan interest of 10% per month.